2015
DOI: 10.1096/fj.14-266064
|View full text |Cite
|
Sign up to set email alerts
|

Novel role for retinol-binding protein 4 in the regulation of blood pressure

Abstract: Elevated levels of serum retinol-binding protein 4 (RBP4) contribute to insulin resistance and correlate with increased prevalence of hypertension and myocardial infarction. We sought to determine whether lowering RBP4 would improve blood pressure (BP) and protect against obesity-or angiotensin (Ang)-II-induced hypertension. Systolic and diastolic BP were lower in the RBP4-knockout (RBP4-KO) mice and higher in the RBP4-overexpressing (RBP4-Tg) mice compared with BP in the wild-type (WT) littermates. Carbachol-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…We observed that circulating RBP4 levels were positively associated with LVMI and LAD. These findings are in line with 2 previous experimental studies that reported an association between RBP4 and cardiac hypertrophy 9, 12. However, our observations are in contrast to another report that noted lack of any association of circulating RBP4 with echocardiographic traits (including LVM) in a moderately sized elderly cohort of men 20.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that circulating RBP4 levels were positively associated with LVMI and LAD. These findings are in line with 2 previous experimental studies that reported an association between RBP4 and cardiac hypertrophy 9, 12. However, our observations are in contrast to another report that noted lack of any association of circulating RBP4 with echocardiographic traits (including LVM) in a moderately sized elderly cohort of men 20.…”
Section: Discussionsupporting
confidence: 91%
“…In this context, it is noteworthy that the adipose tissue is an endocrine tissue which secretes hormones (referred to as adipokines) that mediate several of the cardiometabolic consequences of obesity. Several adipokines have receptors on cardiac myocytes,7, 8, 9 exhibit prohypertrophic and antihypertrophic effects on the myocardium,10, 11, 12, 13 and have been associated with risk of overt HF 14. Prior investigations relating adipokines to cardiac structure and function have focused on single adipokines10, 11, 15, 16, 17, 18, 19, 20, 21 and related them to traditional measures of cardiac remodeling (such as LV mass [LVM]).…”
mentioning
confidence: 99%
“…It has been shown that RBP4 is upregulated in insulin‐resistant conditions associated with obesity and provokes IR by interfering with insulin receptor substrate 1 (Gerrits et al., ; Yang et al., ). In addition, it seems to be a predictor of cardiovascular disease (Alkharfy, Al‐Daghri, Vanhoutte, Krishnaswamy, & Xu, ) and development of atherosclerosis, as it promotes atherogenic dyslipidaemia (Rocha et al., ) and is involved in the regulation of hypertension (Kraus et al., ). Recently, it has been established that RBP4 levels in gingival crevicular fluid and serum are positively correlated with body mass index (BMI) and periodontal parameters (Kanoriya, Pradeep, Mallika, Singhal, & Garg, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that RBP4 is upregulated in insulin-resistant conditions associated with obesity and provokes IR by interfering with insulin receptor substrate 1 (Gerrits et al, 2012;Yang et al, 2005). In addition, it seems to be a predictor of cardiovascular disease (Alkharfy, Al-Daghri, Vanhoutte, Krishnaswamy, & Xu, 2012) and development of atherosclerosis, as it promotes atherogenic dyslipidaemia (Rocha et al, 2013) and is involved in the regulation of hypertension (Kraus et al, 2015).…”
mentioning
confidence: 99%
“…Previous experimental studies have revealed the pro‐hypertrophic function of RBP4 in heart. Kraus et al . found that angiotensin‐II induced cardiac hypertrophy was reduced in RBP4 knockout mice.…”
Section: Discussionmentioning
confidence: 99%